Performance comparison between PD-Fuzzy and PID controller towards the stability of the extendable double-link two-wheeled mobile robot - Abdul Rahman, Muhammad Taqiuddin; Ahmad, Salmiah (IEEE, 2015)
This paper presents a comparison between the Proportional-Derivative (PD)-Fuzzy and Proportional-Integral-Derivative (PID) for balancing control of an extendable doublelink of two-wheeled mobile robot (TWMR). The two controllers were implemented to the first link of the TWMR for performance comparison between the intelligent and conventional controller while maintaining similar control strategies for the rest of the subsystems (second link and extendable-link). The sensors fusion of the Inertial Measurement Unit (IMU) sensor from different subsystems were used to get the angular position of the first link and the second link while the existing disturbance was minimized by applying Kalman filter. The fact is that the variations of the angular position of the second link and the linear motion of the extendable link will affect the balancing of the first link. The accelerometer was used to measure the set point angular position of the first link to guarantee stabilization. The performances of the PD-Fuzzy and PID controllers were examined in terms of the input tracking. The experimental results show that the PD-Fuzzy controller has produced better performances in terms of settling time as compared to the PID controller.